2019
DOI: 10.1111/head.13657
|View full text |Cite
|
Sign up to set email alerts
|

Does Mindfulness‐Based Cognitive Therapy for Migraine Reduce Migraine‐Related Disability in People with Episodic and Chronic Migraine? A Phase 2b Pilot Randomized Clinical Trial

Abstract: Objective The current Phase 2b study aimed to evaluate the efficacy of mindfulness‐based cognitive therapy for migraine (MBCT‐M) to reduce migraine‐related disability in people with migraine. Background Mindfulness‐based interventions represent a promising avenue to investigate effects in people with migraine. MBCT teaches mindfulness meditation and cognitive‐behavioral skills and directly applies these skills to address disease‐related cognitions. Methods Participants with migraine (6‐30 headache days/month) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 63 publications
4
106
2
5
Order By: Relevance
“…Conversely, MOH patients undergoing WT reported a high tendency to experiential avoidance, and they also reported higher psychological inflexibility than the population of the AAQ-II validation study, suggesting acceptance and values-based action as relevant psychological dimensions to be fostered through appropriate psychological strategies for patients with MOH. Recently, Acceptance and Commitment Therapy (ACT) showed promising results in reducing adverse impact in chronic pain conditions, including patients with migraine [32,[70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, MOH patients undergoing WT reported a high tendency to experiential avoidance, and they also reported higher psychological inflexibility than the population of the AAQ-II validation study, suggesting acceptance and values-based action as relevant psychological dimensions to be fostered through appropriate psychological strategies for patients with MOH. Recently, Acceptance and Commitment Therapy (ACT) showed promising results in reducing adverse impact in chronic pain conditions, including patients with migraine [32,[70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…The patients definite answer on receiving psychological strategies is a positive starting point to make complementary behavioral interventions available. In the literature, the recognition of the role of psychosocial aspects in migraine is increasing, with a definite interest in psychological approaches to be integrated with pharmacological and medical ones and a growing interest in, and utilization of, complementary and integrative strategies, such as mindfulness-based interventions [37,38,73]. However, a gap between research on the relevance and effectiveness of behavioral treatment interventions and the clinical practice remains [37,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…People with lower resilience are at risk for greater emotional difficulties such as depression and anxiety, particularly when associated with chronic pain conditions such as migraine. Also, studies on the use of mindfulness and ACT in migraine have demonstrated improvement in patients’ ability to tolerate pain, reduce the use of symptomatic medications and to modulate specific characteristics of the migraine personality (rigidity, low acceptance, and low resilience) . Recently, the calcitonin gene‐related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine .…”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%
“…Also, studies on the use of mindfulness and ACT in migraine have demonstrated improvement in patients' ability to tolerate pain, reduce the use of symptomatic medications and to modulate specific characteristics of the migraine personality (rigidity, low acceptance, and low resilience). 1,[7][8][9] Recently, the calcitonin gene-related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine. 10,11 Real-world experiences with some of these drugs are just being published.…”
mentioning
confidence: 99%
“…52,53 The related approach of Mindfulness-Based Cognitive Therapy seems to also have value for reducing headache disability. [54][55][56] A series of laboratory investigations has been carried out to test the TAMH. Three studies using 3 different empirically validated triggers -visual disturbance, 57 noise, 58 and stress 59 -exposed headache sufferers to triggers for varying durations.…”
Section: How Do Triggers Acquire the Capacity To Precipitate Headaches?mentioning
confidence: 99%